Teachers' experiences in the implementation of the technology education curriculum in one secondary school in the St. George East District in Trinidad - Davis, Eleanor (My University, 2012)
This study sought to examine the facilitating and inhibiting factors that affected teachers during the implementation of the technology education curriculum at a secondary school in Trinidad and Tobago. It also sought to determine the strategies used in coping with the innovation. Data were collected through interviews held with three teachers, as well as through observations and document analysis. The findings revealed that the Ministry of Education, represented by Curriculum Officers, facilitated the implementation process, which was fraught with challenges of disparity in subject content knowledge, content purported by two different training bodies, and management of limited resources
Keywords: Curriculum implementation; Educational innovation; Technology education; Secondary school teachers; Secondary school curriculum; Trinidad and Tobago